Strategic human resource management : formulating and implementing HR strategies for a competitive advantage - Das Gupta, Ananda (Routledge, 2024)
This book puts emphasis on understanding the role of HRM between organizations and people and provides an analytical approach toward encompassing HRM, employment relations, and organizational behavior. As a management discipline, HRM draws insights, models and theories from cognate disciplines and applies them to real-world settings. Further, this book discusses how current theoretical perspectives and frameworks (e.g., those related to strategic competitiveness, knowledge management, learning organization, communities of practice, etc.) can be applied by reflective practitioners to create an eco-friendly organizational culture.